Riqueza e padrões de distribuição dos lagartos de domínio morfoclimático da caatinga - Delfim, Fagner Ribeiro (2012)
The Morphoclimayic Domain of Caatinga remained for years as one of the regions of lower scientific interest in Brazil. The idea that its fauna was poor of endemism and depleted contributed to this lack of interest until about the beginning of the 90 s. Currently, we know that the Caatinga has a relatively rich fauna and is composed of endemic elements. However, much of their territory, especially its core area, continues to show a poor sampling for herpetofauna. This study presents results on the composition and species richness of the lizards in the Caatinga, their distribution patterns and their relationship with the subdivisions of ecoregions domain. This is basically the first study with the lizard fauna treating the Caatinga as a domain morphoclimatic and incorporating data related to enclaves of other vegetation types inserted in its limits. We recorded 78 species of lizards distributed in 12 families (1 Iguanidae, 1 Hoplocercidae, 4 Polychrotidae, 4 Leiosauridae, 17 Tropiduridae, 4 Gekkonidae, 4 Phyllodactylidae, 1 Sphaerodactylidae, 2 Anguidae, 8 Teiidae, 25 Gymnophthalmidae and 7 Scincidae). Through analyzes with data of species distribution, we identified seven centers of endemism. The marginal areas of Caatinga proved richer than their nuclear area, probably due to the influence of neighboring domains. We propose priority areas for scientific research in general. However, further studies are needed to define them more specifically.